Adaptive radiotherapy in locally advanced head and neck cancer: The importance of reduced margins - Hedda Enocson; André Haraldsson; Per Engström; Sofie Ceberg; Maria Gebre-Medhin; Gabriel Adrian; Per Munck af Rosenschöld (Physics and Imaging in Radiation Oncology)
Background and Purpose: Adaptive radiotherapy (ART) involves treatment re-planning based on anatomical changes, which may improve target coverage and sparing of organs-at-risk (OARs). This study retrospectively assessed the technical feasibility and potential benefits of daily ART in combination with reduced planning target volume (PTV) margins for head and neck squamous cell carcinoma (HNSCC). Materials and Methods: Thirty-one patients, encompassing 902 treatment fractions, treated with radiotherapy to 60.0–68.0 Gy in 2 Gy/fraction were studied. Synthetic CTs (sCT) from daily kVCT images were created and contours propagated using deformable image registration (DIR). Target contours were reviewed and corrected. On the sCT, non-adapted delivered doses and ART-plans with 5 mm (clinical standard) and 2 mm PTV-margin were evaluated. All daily dose distributions were then accumulated. Results: Target contours required correction in 48 % of the fractions. Daily non-adapted D98%,CTV was > 95 % in 890 (5 mm) and 825 (2 mm) out of 902 fractions. All adapted plans achieved D98%,CTV > 95 %. Significant reductions in mean doses to OARs were observed for PTV = 2 mm ART-plans: 4.1 Gy for parotid, 2.6 Gy for submandibular, 3.3 Gy for oral cavity, 4.0 Gy for esophagus, and 3.8 Gy for larynx. Conclusion: ART-planning on sCT and DIR propagated contours was feasible and promising for further clinical testing. To obtain a potential clinical benefit of ART, a synchronous reduction of the PTV-margin was warranted. Daily ART can be used to maintain adequate target dosimetry for every fraction, though for the accumulated treatment, insufficient target coverage without ART is unlikely to occur.